Loan Recovery Procedures in Tanzania: A Case of Selected Microfinance Institutions in Dar-Es-Salaam, Tanzania - Sikira, Richard (International Journal of Scientific Research and Management (IJSRM), 2021)
The study aimed to determine the procedures employed by MFIs, specifically in loan recovery in Tanzania. Loan recovery has been a difficult task for many financial institutions but becomes more challenging to microfinance institutions due to the nature and processes they employ. The study examined the loan recovery procedures at NFBS, SMF and AML found in Dar-Es-Salaam, Tanzania. The researcher employed a mixed- case study design, which involved 50 credit officer respondents obtained under the purposive sampling. The study used semi-structured questionnaires to gather primary data and also secondary data from documents available at NFBS, SMF and AML. Data were analysed using simple descriptive statistics with percentages and frequencies for quantitative data, while thematic analysis was used for qualitative data. The study found that NFBS, SMF and AML used loan recovery procedures such as direct contact, friendly reminder, and issuance of final demand notice. Another procedure is to inform the local government on property selling and using a debt collection agency. The study recommends for MFIs to establish and prefer formal procedures that can be used for loan recovery because the use of informal procedures creates room for conflict and leads to ineffectiveness of recovering loans.